Using Mind Mapping Learning Methods for Children’s Language Skills - Sitti Rahmaniar Abubakar; Aprillianti; Hidayat, Ahid; Gadafi, Muamal; Sahriana, Nanang (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
Language skills are significant predictors of early academic and social-emotional outcomes of children and are important predictors of school readiness. This study aims to improve children's language skills through the application of mind mapping learning methods. This classroom action research used Kemmis and Taggart's cycle model. The research subjects were 12 children in group B consisting of eight boys and four girls. The data was collected through observation, interviews, and documentation with the validity of the data using source triangulation and method triangulation. This research uses data analysis techniques in the form of data condensation, data presentation, and drawing conclusions. The results showed that the children's language skills through the application of the mind mapping method in the first cycle were 75%, and in the second cycle had increased to 92%. Based on the results of teacher observations in the implementation of cycle I, the children's language skills obtained a percentage value of 61.5%, and in cycle II increased to 92.3%. While the results of observations of children's activities in the implementation of the first cycle obtained a percentage of 54%, and in the second cycle, it increased to 85%. This study found that the teacher's assessment of this mind mapping method was an easy method to understand so that it was easy to apply in classroom learning. The implication of this research is that it is necessary to carry out further research on the application of the mind mapping method for other aspects of development. Keywords: Early Childhood, language Skills, Mind Mapping Learning Methods References: Abi-El-Mona, I., & Adb-El-Khalick, F. (2008). The influence of mind mapping on eighth graders’ science achievement. School Science and Mathematics, 108(7), 298–312. https://doi.org/10.1111/j.1949-8594.2008.tb17843.x Alamsyah, M. (2019). Kiat jitu meningkatkan prestasi dengan mind mapping (A. Safa, Ed.; 2nd ed.). Mitra Pelajar. Arimbi, Y. D., Saparahayuningsih, S., & Ardina, M. (2018). Meningkatkan Perkembangan Kognitif Melalui Kegiatan Mind Mapping. Jurnal Ilmiah Potensia, 3(2), 64–71. Aykac, V. (2014). An application regarding the availability of mind maps in visual art education based on active learning method. Procedia - Social and Behavioral Sciences, 174, 1859–1866. https://doi.org/10.1016/ j.sbspro.2015.01.848. Balim, A. G. (2013). The effect of mind-mapping applications on upper primary students success and inquiry-learning skills in science and environment education. International Research in Geographical and Environmental Education, 22(4), 337–352. https://doi.org/10.1080/10382046.2013.826543 Batdi, V. (2015). A Meta-analysis Study of Mind Mapping Techniques and Traditional Learning Methods. The Anthropologist, 20(1–2), 62–68. https://doi.org/10.1080/09720073.2015.11891724 Berman, R. A. (2007). Developing Linguistic Knowledge and Language Use Across Adolescence. In E. Hoff & M. Shatz (Eds.), Blackwell Handbook of Language Development (pp. 347–367). Blackwell Publishing Ltd. https://doi.org/10.1002/9780470757833.ch17 Bishop, D. V. M., Snowling, M. J., Thompson, P. A., Greenhalgh, T., & and the CATALISE-2 consortium. (2017). Phase 2 of CATALISE: A multinational and multidisciplinary Delphi consensus study of problems with language development: Terminology. Journal of Child Psychology and Psychiatry, 58(10), 1068–1080. https://doi.org/10.1111/jcpp.12721 Botting, N., & Conti-Ramsden, G. (2000). Social and behavioural difficulties in children with language impairment. Child Language Teaching and Therapy, 16(2), 105–120. https://doi.org/10.1177/026565900001600201 Budd, J. W. (2004). Mind maps as classroom exercises. Journal of Economic Education, 35(1), 35–46. https://doi.org/10.3200/JECE.35.1.35-46 Budyawati, L. P. I. (2016). Implementasi Metode Mind Mapping untuk Meningkatkan Kemampuan Bercerita Anak kelas B di PAUD Sarin Rare Mas Ubud. Pancaran, 5(3), 1–16. Buzan, T. (2005). Mind map: The ultimate thinking tool. Thorston. Buzan, Tony. (2005). Buku Pintar Mind Map. Gramedia Pustaka Utama. Buzan, Tony. (2007). Buku Pintar Mind Map untuk Anak. Gramedia Pustaka Utama. Chang, Y. H., Chang, C. Y., & Tseng, Y. H. (2010). Trends of science education research: An automatic content analysis. Journal of Science Education and Technology, 19(4), 315–331. https://doi.org/10.1007/s10956-009-9202-2 Chiou, C. C. (2008). The effect of concept mapping on students’ learning achievements and interests. Innovations in Education and Teaching International, 45(4), 375–387. Chow, J. C., & Jacobs, M. (2016). The role of language in fraction performance: A synthesis of literature. Learning and Individual Differences, 47, 252–257. https://doi.org/10.1016/j.lindif.2015.12.017 Chularut, P., & DeBacker, T. K. (2004). The influence of concept mapping on achievement, self-regulation, and self-efficacy in students of English as a second language. Contemporary Educational Psychology, 29(3), 248–263. https://doi.org/10.1016/j.cedpsych.2003.09.001 Clegg, J., Law, J., Rush, R., Peters, T. J., & Roulstone, S. (2015). The contribution of early language development to children’s emotional and behavioural functioning at 6 years: An analysis of data from the Children in Focus sample from the ALSPAC birth cohort. Journal of Child Psychology and Psychiatry, 56(1), 67–75. https://doi.org/10.1111/jcpp.12281 Davies, M. (2011). Concept mapping, mind mapping and argument mapping: What are the differences and do they matter? Higher Education, 62, 279–301. https://doi.org/10.1007/s10734-010-9387-6. DePorter, B., & Hernacki, M. (2015). Quantum Learning: Membiasakan Belajar Nyaman dan Menyenangkan. Kaifa. Dhieni, N. (2008). Metode Pengembangan Bahasa. Universitas Terbuka. Dhindsa, HS., M., K., & Anderson, OR. (2011). Constructivist-visual mind map teaching approach and the quality of students’ cognitive structures. Science Education Technology, 20, 186–200. https://doi.org/10.1007/s10956-010- 9245-4. Duff, F. J., Reen, G., Plunkett, K., & Nation, K. (2015). Do infant vocabulary skills predict school‐age language and literacy outcomes? Journal of Child Psychology and Psychiatry, 56(8), 848–856. https://doi.org/10.1111/jcpp.12378 Farrand, P., Fearzana, H., & Hennessy, E. (2002). The efficacy of the mind map study technique. Medical Education, 36, 426–431. Hapidin, H., Pujianti, Y., & Juniasih, I. (2019). The The Effectiveness of Using Mind Mapping Method to Improve Child Development Assessment. JPUD - Jurnal Pendidikan Usia Dini, 13(1), 172–186. https://doi.org/10.21009/10.21009/jpud.131.13 Hendarwati, E. (2015). Peningkatan Kemampuan Bahasa Melalui Mind Mapping pada Anak TK Aisyah 29 Surabaya. Jurnal Didaktis, 12(1). Hoff, E. (2013). Interpreting the early language trajectories of children from low-SES and language minority homes: Implications for closing achievement gaps. Developmental Psychology, 49(1), 4–14. https://doi.org/10.1037/a0027238 Holley, C. D., Dansereau, D. F., McDonald, B. A., Garland, J. C., & Collins, K. W. (1979). Evaluation of a hierarchical mapping technique as an aid to prose processing. Contemporary Educational Psychology, 4(3), 227–237. https://doi.org/10.1016/0361-476X(79)90043-2 Horton, P. B., McConney, A. A., Gallo, M., Woods, A. L., Senn. G. J., & Hamelin, D. (1993). An investigation of the effectiveness of concept mapping as an instructional tool. Science Education, 77, 95–111. Hulme, C., Nash, H. M., Gooch, D., Lervåg, A., & Snowling, M. J. (2015). The Foundations of Literacy Development in Children at Familial Risk of Dyslexia. Psychological Science, 26(12), 1877–1886. https://doi.org/10.1177/0956797615603702 Indriyani, M. P., Wirya, I. N., & Parmiti, D. P. (2013). Penerapan metoda mind mapping berbantuan media. Jurnal Pendidikan Anak Usia Dini Undiksha, 1(1), 1–10. Jalongo, M. R. (2014). E arly Childhood Language Arts (6th ed.). Pearson Education, Inc. Jones, B. D., Ruff, C., Tech, V., Snyder, J. D., Tech, V., Petrich, B., Tech, V., & Koonce, C. (2012). The Effects of Mind Mapping Activities on Students ’ Motivation. International Journal for the Scholarship of Teaching and Learning, 6(1). Karpicke, J. D., & Blunt, J. R. (2011). Retrieval practice produces more learning than elaborative studying with concept mapping. Science, 331(6018), 772–775. https://doi.org/10.1126/science.1199327 Keles, O. (2012). Elementary teachers’ views on mind mapping. International Journal of Education, 4(1), 93–100. Kemmis, S., McTaggart, R., & Nixon, R. (2014). The Action Research Planner. Springer Singapore. https://doi.org/10.1007/978-981-4560-67-2 Law, J., Rush, R., Schoon, I., & Parsons, S. (2009). Modeling developmental language difficulties from school entry into adulthood: Literacy, mental health, and employment outcomes. Journal of Speech, Language, and Hearing Research : JSLHR, 52 6, 1401–1416. Lestari, N. G. A. M. Y. (2020). Penerapan Metode Mind Map Dalam Pengembangan Kreativitas Anak Usia Dini. Pratama Widya: Jurnal Pendidikan Anak Usia DIni, 5(1), 35–42. Locke, A., Ginsborg, J., & Peers, I. (2002). Development and disadvantage: Implications for the early years and beyond. International Journal of Language & Communication Disorders, 37(1), 3–15. https://doi.org/10.1080/13682820110089911 Madu, BC., & Metu, IC. (2010). Effect of mind map as a notetaking approach on students’ achievements’ in economics. Journal of Emerging Trends in Economics and Management Sciences (JETEMS), 3(3), 247–251. McGillion, M., Pine, J. M., Herbert, J. S., & Matthews, D. (2017). A randomised controlled trial to test the effect of promoting caregiver contingent talk on language development in infants from diverse socioeconomic status backgrounds. Journal of Child Psychology and Psychiatry, 58(10), 1122–1131. https://doi.org/10.1111/jcpp.12725 Meier, PS. (2007). Mind-mapping. Social Research, 52, 1–4. Merchie, E., & Van Keer, H. (2016). Mind mapping as a meta-learning strategy: Stimulating pre-adolescents’ textlearning strategies and performance? Contemporary Educational Psychology, 46, 128–147. https://doi.org/10. 1016/j.cedpsych.2016.05.005 Mona, IA., & Khlaick, FA. (2008). The influence of mind mapping on eighth graders’ science achievement. School Science and Mathematics, 108(7), 298–312. https://doi.org/10.1111/j.1949-8594.2008.tb17843.x Nesbit, J. C., & Adesope, O. O. (2006). Learning with concept and knjowledge maps: A meta-analysis. Review of Educational Research, 76(3), 413–448. Novak, J. D., & Gowin, D. B. (1984). Learning how to learn. Cambridge University Press. O‟Donnell, A. M., Dansereau, D. F., & Hall, R. H. (2002). Knowledge maps as scaffolds for cognitive processing. Educational Psychology Review, 14, 71–86. Olivia, F. (2013). 5—7 Menit Asyik Mind Mapping Kreatif. Elex Media Computindo. Pace, A., Alper, R., Burchinal, M. R., Golinkoff, R. M., & Hirsh-Pasek, K. (2019). Measuring success: Within and cross-domain predictors of academic and social trajectories in elementary school. Early Childhood Research Quarterly,46, 112–125. https://doi.org/10.1016/j.ecresq.2018.04.001 Padang, J. S. M., & Gurning, B. (2014). Improving Students’ Achievement in Writing Descriptive Text through Mind Mapping Strategy. Register Journal of English Language Teaching of FBS-Unimed, 3, 1–11. Patmonodewo, S. (2000). Pendidikan Anak Pra Sekolah. Rineka Cipta. Paxman, CG. (2011). Map your way to speech success! Employing mind mapping as a speech preparation technique. Communication Teacher, 25(1), 7–11. https://doi.org/10.1080/17404622.2010.513994 Riswanto, & Putra, P. P. (2012). The Use of Mind Mapping Strategy in the Teaching of Writing at SMAN 3 Bengkulu , Indonesia. International Journal of Humanities and Social Science, 2(21), 60–68. Saed, H. A., & AL-Omari, H. A. (2014). The Effectiveness of a Proposed Program Based on a Mind Mapping Strategy in Developing the Writing Achievement of Eleventh Grade EFL Students in Jordan and Their Attitudes Towards Writing. Journal of Education and Practice, 5, 88–109. San Risqiya, R. (2013). The Use of Mind Mapping in Teaching Reading Comprehension. ELTIN Journal, 1, 32–43. Serig, D. (2011). Beyond brainstorming: The mind map as art. Teaching Artist Journal, 9(4), 249–257. Somers, MJ., Passerini, K., Parhankangas, A., & Casal, J. (2014). Using mind maps to study how business school students and faculty organize and apply general business knowledge. The International Journal of Management Education, 12, 1–13. Warsidi, Burhanuddin, A., & Mustafa, M. (2014). A Collaboration Of Mind Mapping And Organizational Pattern To Improve Students ’ Essay Writing Ability. Jurnal Pasca Unhas, 11, 1–12. Whitehurst, G. J., & Fischel, J. E. (1994). Practitioner Review: Early Developmental language Delay: What. If Anything. Should the Clinician Do About It? Journal of Child Psychology and Psychiatry, 35(4), 613–648. https://doi.org/10.1111/j.1469-7610.1994.tb01210.x Williams, M. H. (2012). Physical webbing: Collaborative kinesthetic three-dimensional mind maps. Active Learning in Higher Education, 13(1), 35–49. https://doi.org/10.1177/1469787411429185 Willis, C. L., & Miertschin, S. L. (2006). Mind maps as active learning tools. Journal of Computing Sciences in Colleges, 21(4), 266–272. Yunus, M. M., & Chien, C. H. (2016). The Use of Mind Mapping Strategy in Malaysian University English Test (MUET) Writing. Creative Education, 07(04), 619–626. https://doi.org/10.4236/ce.2016.74064